METABOLIC PLASMATIC BIOMARKER AS A RELEVANT INDICATOR FOR ALVEOLAR BONE RESORPTION CONSECUTIVE TO DENTURES RELINING - Dana Gabriela Budală; Dragoș Ioan Virvescu; Monica Mihaela Scutariu; Zinovia Surlari; Dragoș Nicolae Frățilă; Mihaela Scurtu; Ionuț Luchian (Romanian Dental Association for Education, 2022)
Introduction. Complete denture relines are typically necessary due to ontinuous bone resorption. Because to individual differences in resorption rates, the time between relining procedures varies. As of right now, there are no predictors to help identify people who may need relines frequently or to help advise doctors when they make reline decisions.